Toxicity and bacterial anti-motility activities of the hydroethanolic extract of Acacia senegal (L.) Willd (Fabaceae) leaves - René Dofini Magnini; Mathieu Nitiéma; Geoffroy G. Ouédraogo; Sylvain Ilboudo; Alimata Bancé; Hassanata Millogo-Koné; Carole Di Giorgio; Jean-Marie Pagès; Adama Hilou; Anne Davin-Regli (BMC, 2021)
Abstract Background Acacia senegal is a plant traditionally used for its various properties, including the treatment of infectious diseases. Recently, our team has demonstrated the ability of the hydroethanolic extract of the leaves to increase the activity of phenicol antibiotics against multi-resistant bacteria. The aim of this work is to determine the toxicological effects of the extract and its capacity to inhibit the bacterial mobility of Gram-negative bacteria, in order to evaluate the level of safety use of this plant. Methods The cytotoxicity test was performed using the neutral red absorption method. Acute and sub-acute oral toxicity were conducted on NMRI mice and Wistar rats. The behaviour and adverse effects were recorded during the 14 days of the acute study. For the subacute test, biochemical parameters, food and water consumption, and morphological parameters were determined. The anti-motility activities were evaluated on Pseudomonas aeruginosa PA01 and Escherichia coli AG100, using specific concentrations of Agar as required by the method. Results HEASG induced inhibition of keratinocytes cell growth with an IC50 of 1302 ± 60 μg/mL. For the acute toxicity study in mice, the single dose of extract of 2000 mg/kg body weight caused no deaths and no behavioural changes were observed; therefore, the median lethal dose (LD50) of HEASG was calculated to 5000 mg/kg body weight. In Wistar rats, no mortality was observed at 250, 500 and 1000 mg/kg/day during the 28-day subacute oral toxicity study. The weights of both females and males increased globally over time, regardless of the batch. No statistically significant differences were registered for organ weights and biochemical parameters, except for chloride for biochemical parameters. Water and food consumption did not change significantly. Furthermore, no macroscopic changes in organ appearance were observed. Regarding anti-motility activity, the extract has reduced the swarming motility of PA01 and AG100 significantly at the concentration of 32 μg/mL (P < 0.001). The extract has reduced the swimming motility (P < 0.01) of PA01 but not AG100. Conclusions The results suggest that hydroethanolic extract of A. senegal leaves has significant activity against bacterial motility and relatively low toxicity.